Anesthesia and simulated transport of two Amazonian fish with three different basil (Ocimum sp.) essential oils - Isabelle Santos Silva; Orlando Pinto de Almeida Castro Neto; Patrick Jordan Correia-Silva; Raissa Yannick Couto Rocha; Aila Queiroz da Hora; Carlos Eduardo Copatti (Revista Brasileira de Saúde e Produção Animal)
ABSTRACT This study aimed to evaluate the anesthetic induction and transportation of freshwater angelfish (Pterophyllum scalare) and tambaqui (Colossoma macropomum) (both Amazonian fish) juveniles using three basil essential oils (EO): Ocimum sanctum (EOOSE) (Eugenol 58.94%), Ocimum canum (EOOCL) (Linalool 68.64%), and Ocimum basilicum (EOOBM) (Methyl chavicol 68.67%). The concentrations used were: 0 (control), 10, 25, 50, 100, 200, 300, 400 (only for EOOCL and EOOBM), 600 and 800 (both only for EOOBM) µL L-1. In another experiment, concentrations of 0 (control), 10, and 20 µL L−1 were tested for simulated transport during 6 h. There was only sedation for the fish with the three EO tested in concentrations up to 25 µL L-1. In this order, for freshwater angelfish, anesthesia and recovery times of less than 3 and 10 min, respectively, were found from 200, 400, and 800 µL L-1 for EOOSE, EOOCL, and EOOBM. For tambaqui, following these same assumptions, the concentrations indicated for EOOSE, EOOCL, and EOOBM were 200, 300, and 400 µL L-1, respectively. It is concluded that for sedation and transport of fish, 10 and 20 µL L-1 can be used (regardless of the EO), and for rapid anesthesia, 200 µL L-1 of EOOSE is indicated.